Phytochemistry and Pharmacology of Trachyspermum ammi - Akram, Muhammad; Rehman, Urooj; Ahmed, Misbah (African Journal of Sciences and Traditional Medicine, 2025)
Trachyspermum ammi is a member of the family Apiaceae. The majority of medical uses for seeds and roots are as spices and diuretics, respectively. Ajwain oil, a dark oil, is found in seeds. This oil is used to treat respiratory conditions, gastrointestinal problems, and hunger disorders. The oil exhibited antibacterial, antifungal, and anti-aggregatory properties. On the other hand, ajwain is a traditional potential herb that is used for a number of ailments. The fruit possesses carminative, antispasmodic, stimulant, and anti-diarrheal properties.